Diagnostic accuracy of periapical radiograph, cone beam computed tomography, and intrasurgical measurement techniques for assessing furcation defects / Nurul Ain Mohamed Yusof - Mohamed Yusof, Nurul Ain (2020)
The periapical radiograph (PA), which conventionally used as an adjunct in the diagnosis of molar with furcation involvement (FI) may lead to inaccuracy in furcation analysis. Cone beam computed tomography (CBCT) is increasingly used in the periodontology field to overcome the limitations of conventional radiographs. However, the difference in the accuracy of the measurement of furcation defects between PA and CBCT remains unclear. Hence, this study aims to evaluate the accuracy of CBCT, PA, and intrasurgical measurement techniques in the assessment of molars with furcation defects. This parallel, single-blinded, randomised controlled trial (RCT) consisted of 22 periodontitis patients who had molar with advanced FI. All patients followed the same inclusion criteria and were treated following the same protocol, except for radiographic taking (CBCT vs. PA). This study proposed and evaluated five parameters that represent the extent and severity of furcation defects in molars teeth, including CAL (clinical attachment loss), BL-H (bone loss in horizontal direction), BL-V (bone loss in vertical direction), RT (root trunk), and FW (width of the furcation defect). Intrasurgical measurements of furcation defects were compared with CBCT and PA-based data measurement. The results showed there were no statistically significant differences between the CBCT and intrasurgical measurements for any clinical parameter (p > 0.05). However, there were statistically significant differences in all measurements (p < 0.05) except for the RT parameter between PA and intrasurgical measurements. The majority of the measurements from CBCT and PA were underestimated when compared to the intrasurgical measurements. Meanwhile, the sensitivity were 62.8% and 56.9% for CBCT and periapical, respectively. In conclusion, when compared to the intrasurgical measurements, CBCT provided better diagnostic, sensitivity, and quantitative information on CAL, height, depth, and width of the furcation defects than PA.